Interventions for reading problems : designing and evaluating effective strategies - Daly, Edward J.; Neugebaurer, Sabina; Chafouleas, Sandra; Skinner, Christopher H. (New York : London : The Guilford Press, 2015)
Presenting a systematic framework for the development of reading skills, this title concentrates on those students who have difficulty in complying with literacy standards, as well as increasing their awareness, fluency and comprehension.
Includes bibliographical references and index.
Keywords: Reading -- Remedial teaching